2013
DOI: 10.22201/fe.01851667p.2012.280.37336
|View full text |Cite
|
Sign up to set email alerts
|

La Ley De Okun en México: Una Mirada De Género, 2000.2-2011.1

Abstract: Con base en la estimación del modelo de primeras diferencias de Okun (1962) demostramos empíricamente que existe un diferencial en el crecimiento del producto de México a partir del desempleo de mujeres y hombres, lo cual sugiere la existencia de productividades diferentes por sexo. Para ello estimamos un modelo de vectores autoregresivos irrestrictos (UVAR por sus siglas en inglés) con impulsos generalizados apoyado por una regresión lineal (2000.2-2011.1). También encontramos que el crecimiento económico red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Similar results were found by Rodríguez and Peredo (2007). Loría et al (2012) estimated the growth-rate version of Okun's law by using a disaggregated unemployment rate by gender, and their results show that, in Mexico, economic growth immediately has a negative impact on male unemployment, whereas for women the effect is slower but stronger. They also found that male unemployment has a stronger impact on economic growth.…”
Section: Okun's First Differences Model and Okun's Lawmentioning
confidence: 99%
“…Similar results were found by Rodríguez and Peredo (2007). Loría et al (2012) estimated the growth-rate version of Okun's law by using a disaggregated unemployment rate by gender, and their results show that, in Mexico, economic growth immediately has a negative impact on male unemployment, whereas for women the effect is slower but stronger. They also found that male unemployment has a stronger impact on economic growth.…”
Section: Okun's First Differences Model and Okun's Lawmentioning
confidence: 99%
“…Islas y Cortez (2018), a partir del trabajo de Jardin y Stephan (2012), plantean que la no linealidad del coeficiente de Okun en México se debe a que en períodos de recesión, en la medida en que el mercado laboral sea flexible, las empresas despiden a sus empleados rápida y agresivamente, y no contratan de la misma forma en períodos de expansión. Esto redunda en que el desempleo se reduzca lentamente en el período de recuperación, por lo que los trabajadores desempleados encuentran una salida en la informalidad (Loría, Aupart y Salas, 2016), sobre todo las mujeres (Loría, Libreros y Salas, 2011).…”
Section: Revisión De Literaturaunclassified
“…Los trabajos sobre la ley de Okun en México no se limitan a una relectura del artículo original (Loría y Ramos, 2007), sino que también se han centrado en atribuir la magnitud del coeficiente de Okun a factores como la flexibilidad laboral (Chavarín, 2001;Loría, Ramírez y Salas, 2015), el género (Loría, Libreros y Salas, 2011), la informalidad (Islas y Cortez, 2018) y la fase del ciclo económico (Islas y Cortez, 2013. Sin embargo, estos trabajos, aun cuando son meritorios por cuanto incorporan variables que enriquecen el análisis original de Okun (1983), no consideran explícitamente la heterogeneidad estructural que existe en las 32 entidades federativas ni los factores que la generan.…”
Section: Revisión De Literaturaunclassified
“…Islas and Cortez (2018), drawing on the work of Jardin and Stephan (2012), posit that the nonlinearity of the Okun coefficient in Mexico derives from the fact that in periods of recession, to the extent that the labour market is flexible, businesses fire employees quickly and aggressively, and do not hire in the same way in periods of expansion. This results in unemployment falling slowly in the recovery period, so that unemployed workers find a way out in informality (Loría, Aupart and Salas, 2016), especially women (Loría, Libreros and Salas, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Papers on Okun's law in Mexico are not limited to a rereading of the original article (Loría and Ramos, 2007), but have also focused on attributing the magnitude of the Okun coefficient to factors such as labour flexibility (Chavarín, 2001;Loría, Ramírez and Salas, 2015), gender (Loría, Libreros and Salas, 2011), informality (Islas and Cortez, 2018) and the phase of the economic cycle (Islas andCortez, 2013 and. However, although these studies are commendable in that they incorporate variables that enrich Okun's original analysis (1983), they do not explicitly consider the structural heterogeneity among the 32 States or the factors behind it.…”
Section: Literature Reviewmentioning
confidence: 99%